2021
DOI: 10.1186/s12879-020-05716-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Long COVID’: persistent COVID-19 symptoms in survivors managed in Lagos State, Nigeria

Abstract: Background Coronavirus disease once thought to be a respiratory infection is now recognised as a multi-system disease affecting the respiratory, cardiovascular, gastrointestinal, neurological, immune, and hematopoietic systems. An emerging body of evidence suggests the persistence of COVID-19 symptoms of varying patterns among some survivors. This study aimed to describe persistent symptoms in COVID-19 survivors and investigate possible risk factors for these persistent symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
131
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(164 citation statements)
references
References 29 publications
25
131
6
2
Order By: Relevance
“…Among the 354 patients included in our cohort study, 36% of patients reported the presence of one or more symptoms after at least 9 months (in the mean) after COVID-19 onset. The most common symptoms were fatigue, dyspnea, and pain symptoms, which is consistent with the literature thus far [ 1 , 2 , 3 , 4 , 11 , 12 , 16 ]. These findings suggested systemic chronic inflammation with abnormal pro-inflammatory cytokine expression, which was observed in patients following COVID-19 [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the 354 patients included in our cohort study, 36% of patients reported the presence of one or more symptoms after at least 9 months (in the mean) after COVID-19 onset. The most common symptoms were fatigue, dyspnea, and pain symptoms, which is consistent with the literature thus far [ 1 , 2 , 3 , 4 , 11 , 12 , 16 ]. These findings suggested systemic chronic inflammation with abnormal pro-inflammatory cytokine expression, which was observed in patients following COVID-19 [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, there have been several reports of patients who reported no return to their previous state of health after having COVID-19 for several weeks or months, with variation in the duration of symptoms and clinical history [ 3 ]. Some authors referred to ‘long COVID-19 syndrome’ [ 2 , 4 , 5 , 6 ], ‘post-COVID-19 syndrome’ [ 7 , 8 ], or ‘post-acute COVID-19 syndrome’ [ 3 , 9 ], a syndrome that can possibly have an impact on the quality of life of patients [ 10 ]. The most common persistent symptoms in COVID-19 are fatigue and breathlessness [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies in the literature investigating post‐COVID symptoms were usually performed in the early period after recovery or in a relatively small number of patients. 3 , 4 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 There is growing concern regarding post‐COVID syndrome, but still little is known. Understanding the prevalence, variety, and duration of the post‐COVID manifestations that are not usually life‐threatening but impair the quality of life, is crucial for the development of follow‐up and treatment strategies in the post‐COVID periods.…”
Section: Discussionmentioning
confidence: 99%
“…This assertion is corroborated by a similar study from Lagos, Nigeria, where 40.6% of hospitalized adults reported symptoms suggestive of PCS. 10 Studies from Europe, the United Kingdom, the United States, and Asia have reported PCS among 32% to 96% of hospitalized COVID-19 patients. [12][13][14][15] Cough, fatigue, and dyspnea were the most common symptoms reported in our cohort.…”
Section: Discussionmentioning
confidence: 99%